Development of Arfi Book Digital Flipbook Learning Media for IPAS Subjects on Traditions and Cultures of the Community Around Me to Improve Learning Outcomes of Fourth-Grade Elementary School Students - Arina Nur Salsabila; Kurniana Bektiningsih (FKIP - Universitas Riau, 2026)
This study aimed to develop and assess the feasibility and effectiveness of ArfiBook, a digital flipbook-based learning media, for teaching IPAS on Traditions and Cultures of the Community Around Me to fourth-grade elementary students. The research employed a Research and Development (R&D) approach, which included stages of needs analysis, media design, development, expert validation, limited-scale trial, and effectiveness testing. Data were gathered through expert evaluation sheets, teacher and student response questionnaires, and pretest-posttest assessments. Analysis focused on media feasibility, practicality in classroom use, and the impact on students’ learning outcomes. The findings revealed that ArfiBook was highly feasible according to both media and subject matter experts and was well-received by teachers and students, indicating strong practicality. Moreover, students’ learning outcomes showed a notable improvement after using the media, demonstrating its effectiveness in supporting IPAS learning. The study concludes that ArfiBook serves as a practical, feasible, and effective learning tool that can enhance engagement and comprehension in elementary school IPAS lessons, offering an innovative approach that aligns with digital learning trends and the need for interactive, student-centered instructional materials.